2016
DOI: 10.1021/acs.macromol.6b01764
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor Porous Conjugated Polymers for Photocatalytic Hydrogen Production: The Importance of Acceptor Comonomer

Abstract: Porous conjugated polymer (PCP) is a new kind of photocatalyst for photocatalytic hydrogen production (PHP). Here, we report the importance of the electronic properties of acceptor comonomer in determining the reactivity of 4,8-di(thiophen-2-yl)benzo[1,2-b:4,5-b′]dithiophene (DBD)-based PCP photocatalyst for PHP application. It was found that the incorporation of nitrogen-containing ligand acceptor monomers into PCP network is an effective strategy to enhance the PHP activity. These moderately electron-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
104
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 33 publications
4
104
0
Order By: Relevance
“…Examples of organic photocatalysts include oligo-and poly(p-phenylene)s [26][27][28][29] and other unbranched conjugated polymers, [30][31][32][33] poly(azomethine)s, 34 triazine-type materials, [35][36][37][38][39][40] covalent organic frameworks, [41][42][43] and a rapidly increasing number of structurally diverse conjugated microporous polymers. 7,[44][45][46][47][48] The activity of these photocatalysts for hydrogen and/or oxygen evolution is a complex function of properties such as the absorption spectrum, the potential of the charge carriers (i.e., the band positions), and the wettability of their surfaces, among other factors. It is challenging to optimize all of these various properties through copolymerisation strategies since they may have contrasting or indeed antagonistic dependencies on the copolymer composition: for example, introduction of polar building blocks might increase the wettability of the polymer while also impacting light absorption in a negative way.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of organic photocatalysts include oligo-and poly(p-phenylene)s [26][27][28][29] and other unbranched conjugated polymers, [30][31][32][33] poly(azomethine)s, 34 triazine-type materials, [35][36][37][38][39][40] covalent organic frameworks, [41][42][43] and a rapidly increasing number of structurally diverse conjugated microporous polymers. 7,[44][45][46][47][48] The activity of these photocatalysts for hydrogen and/or oxygen evolution is a complex function of properties such as the absorption spectrum, the potential of the charge carriers (i.e., the band positions), and the wettability of their surfaces, among other factors. It is challenging to optimize all of these various properties through copolymerisation strategies since they may have contrasting or indeed antagonistic dependencies on the copolymer composition: for example, introduction of polar building blocks might increase the wettability of the polymer while also impacting light absorption in a negative way.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al investigated the photocatalytic activity of as eries of S-andN -containing polymers achieving hydrogen evolution rates of up to 106.9 mmol h À1 withoutt he addition of ac o-catalyst. [17] However,t he report states ar esidual palladium (Pd) content from the Sonogashira-Hagihara cross-coupling of between 0.73 and 2.13 wt %t hat may facilitatet he hydrogen evolution reaction. [18] In our SNPs andN Ps, we detect residual Pd content between 0.13 and 0.02 wt %( one order of magnitude lower than in previous reports) via inductively coupled plasma optical emissions pectrometry (ICP-OES; Supporting Information, Ta ble S5), energy-dispersive X-ray (EDX) spectroscopy (Supporting Information, Table S6), and XPS (Supporting Information, Ta ble S8).…”
mentioning
confidence: 99%
“…The high photocatalytic activity of PrCMP‐3 could be mainly attributed to the high specific surface area and extended π‐conjugation. However, it is still low in comparison with other functionalized CMP photocatalysts, such as spirobifluorene‐containing PCP2e (26 µmol h −1 ), SP‐CMP (28.8 µmol h −1 ), donor–acceptor porous conjugated polymer of PCP11 (106.9 µmol h −1 ), benzothiadiazole‐containing linear polymer of B‐BT‐1,4 (116 µmol h −1 ), dibenzo[b,d]thiophene‐based linear conjugated copolymer photocatalyst (145 µmol h −1 ), and the perylene‐based porous conjugated polymer of PCP3e with bipyridyl acceptor unit (17.8 µmol h −1 ) . The main reason could be attributed to the lack of functional groups in favor of charge transmission in these PrCMPs compared with other organic photocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Then, they developed another series of CMP photocatalysts with different monomer linker length . Yu and co‐workers reported that the CMP photocatalysts with donor segments, fully conjugated backbone and ordered local structure, which are important for charge transport, could exhibit high photocatalytic activity for hydrogen evolution. They also revealed that the residual palladium catalyst plays a key role for the catalytic performance of CMPs.…”
Section: Introductionmentioning
confidence: 99%